2021
DOI: 10.1177/19485506211018151
|View full text |Cite
|
Sign up to set email alerts
|

Is Meta-Accuracy Consistent Across Levels of Acquaintanceship?

Abstract: Some people tend to be especially accurate about the personality impressions they make, but is meta-accuracy a consistent tendency that spans levels of acquaintanceship, or is it only observed within levels of acquaintanceship? Three studies suggested that meta-accuracy is consistent among close others but not across new acquaintances and close others. This pattern was observed for observable and unobservable traits and when accounting for people who made more consistent impressions on others (i.e., high conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Therefore, it is unclear how these results might translate to other populations (e.g., those in long‐distance relationships, same‐gender couples) and other types of relationships (e.g., friends, strangers). Elsaadawy and Carlson (2021) found that meta‐accuracy for personality is moderately correlated across different types of close relationships, but it was not related to meta‐accuracy of first‐impressions. Therefore, perhaps these findings may generalize to other types of close relationships (e.g., friendships) but may not necessarily generalize to first impressions contexts (strangers).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is unclear how these results might translate to other populations (e.g., those in long‐distance relationships, same‐gender couples) and other types of relationships (e.g., friends, strangers). Elsaadawy and Carlson (2021) found that meta‐accuracy for personality is moderately correlated across different types of close relationships, but it was not related to meta‐accuracy of first‐impressions. Therefore, perhaps these findings may generalize to other types of close relationships (e.g., friendships) but may not necessarily generalize to first impressions contexts (strangers).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a globally positive impression and high Agreeableness are the most desirable impressions to make, so perhaps when people do not know an acquaintance well enough to know how that acquaintance feels about them, they rely on their self-views to determine how they are seen on highly desirable impressions. Given that different routes to meta-accuracy likely require a different set of skills and attributes, it makes sense that the people who are good metaperceivers in a first impression interaction are not the same people who are good metaperceivers among close others (Elsaadawy & Carlson, 2022). Future work should identify the skills and attributes that foster accuracy about metapositivity and metaperception substance with new versus close acquaintances to better understand how meta-accuracy can be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most important and informative cues for meta-accuracy may be facial and verbal, which are available in both in-person and video contexts. As such, even though meta-accuracy may not necessarily be consistent across levels of acquaintanceship (e.g., close others vs. strangers; Elsaadawy & Carlson, 2022), the positivity and the accuracy of metaperceptions and their implications could be consistent across different modes of communication. Yet, social anxiety did not predict distinctive meta-accuracy in both contexts, suggesting there may be some differences too.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The extant literature examining metaperceptions in person suggests that people know how positively they are seen by others, evidenced by significant and high levels of meta-positivity (Carlson, 2016a(Carlson, , 2016bElsaadawy & Carlson, 2022;Elsaadawy et al, 2021;Tissera et al, 2021;Tissera & Lydon, 2022). Might people display meta-positivity online and how might these levels compare to inperson interactions?…”
Section: Meta-positivitymentioning
confidence: 99%